Restrictive versus liberal blood transfusion for gastrointestinal bleeding: a systematic review and meta-analysis of randomised controlled trials - Odutayo, A; Desborough, M; Trivella, M; Stanley, A; Dorée, C; Collins, G; Hopewell, S; Brunskill, S; Kahan, B; Logan, R; Barkun, A; Murphy, M; et al. (Elsevier, 2017)
BACKGROUND: Acute upper gastrointestinal bleeding is a leading indication for red blood cell (RBC) transfusion worldwide, although optimal thresholds for transfusion are debated. METHODS: We searched MEDLINE, Embase, CENTRAL, CINAHL, and the Transfusion Evidence Library from inception to Oct 20, 2016, for randomised controlled trials comparing restrictive and liberal RBC transfusion strategies for acute upper gastrointestinal bleeding. Main outcomes were mortality, rebleeding, ischaemic events, and mean RBC transfusion. We computed pooled estimates for each outcome by random effects meta-analysis, and individual participant data for a cluster randomised trial were re-analysed to facilitate meta-analysis. We compared treatment effects between patient subgroups, including patients with liver cirrhosis, patients with non-variceal upper gastrointestinal bleeding, and patients with ischaemic heart disease at baseline. FINDINGS: We included four published and one unpublished randomised controlled trial, totalling 1965 participants. The number of RBC units transfused was lower in the restrictive transfusion group than in the liberal transfusion group (mean difference -1·73 units, 95% CI -2·36 to -1·11, p<0·0001). Restrictive transfusion was associated with lower risk of all-cause mortality (relative risk [RR] 0·65, 95% CI 0·44-0·97, p=0·03) and rebleeding overall (0·58, 0·40-0·84, p=0·004). We detected no difference in risk of ischaemic events. There were no statistically significant differences in the subgroups. INTERPRETATION: These results support more widespread implementation of restrictive transfusion policies for adults with acute upper gastrointestinal bleeding. FUNDING: None.